INFECTIOUS DISEASES IN FARM ANIMALS OF YAKUTIA - L. M. Kokolova; S. I. Isakov; T. A. Platonov; L. Ju. Gavrilyeva; I. I. Grogoryev; Z. K. Ivanova; S. M. Stepanova (Российский паразитологический журнал, 2016)
Features of main infectious diseases in animals of Yakutia are presented. The research was conducted in horse, cattle and deer ranches of Yakutia. 45 horses, 23 cattle, 51 northern deer were investigated in 2001–2010 by the method of complete and incomplete helminthological postmortem examination of intestines and muscles. 3924 fecal samples including 2523 – from horses, 963 – from cattle and 438 – from northern deer were examined by the method of copro- and larvoscopy. 193 helminth species related to 60 genera, 26 families, 10 units, 4 classes, 3 types were detected in domestic animals in Yakutia. Helminthosis take a leading position in general pathology of horses, northern deer and cattle. Northern deer are infected with 37 helminth species, 9 of which are cestode species, 25 – nematode species, 3 – trematode species as well as with gad-fly larvae. For the first time at dehelmintization of herd horses we applied anthelmintic drugs in combination with the probiotic Sakhabactisubtil. A concomitant use of the Equisect and probiotic Sakhabactisubtil contributes to a quicker recovering of qualitative and quantitative composition of intestinal microorganisms and has a positive effect on immune and fermentation systems as well as metabolic functions of growing horses.